Competition or cooperation in public transport - Botond Aba (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Transport, especially public transport has been at the centre of professional attention from time to time. Although the effect of transport innovation shortly appears and it works high effectively in public transport (as you think of the innovation of bus transport and its dynamic progression) the attention is not due to these results, but due to problems of public transport and to strains in its social contradictions. (Sometimes the transport innovation starts already in public transport sector system, for example innovation of subway and high speed train.) Economic crisis especially highlights social contradictions, when the market is decreasing and enterprises are struggling to survive or to hold monopoly status. New enterprises could go on the market or the existing ones could stay in competition only if they are able to influence and convince passengers to choose them by getting on. The third that benefits is often the individual transport, and behind the automobile industry with extended power and influence. My hypothesis is that public transport sector is economically very different to classical categories of market sector, while personal utility and real value do not determine the whole market (included supplies and demands) but the phenomena of pseudo market does it. The sustainability of public transport does not depend on the individual in the sense of passenger, but on the community and on the options of common weal of it. The Institution of Transport Sciences ((KTI)), which celebrated its 70th anniversary in 2008, has been focusing on the market of public transport in the last 8 years, because strain of the market has been realized. The classical orientation of the institute, which was automobile transport and road research, has been widened with railway transport, transport policy and economics research.
Keywords: 330